PENDAMPINGAN UMKM TERDAMPAK COVID-19 DENGAN PEMANFAATAN TEKNOLOGI INFORMASI - Dwi Vernanda; Nunu Nugraha Purnawan; Tri Herdiawan Apandi; Haryati Haryati; Rian Piarna; Mohammad Iqbal; Slamet Rahayu; Nurfitria Khoirunnisa; Wulan Siti Nurul (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
The use of digital media and information technology functioned an important role in the sustainability of micro, small and medium enterprises, especially during the Covid-19 pandemic. The survey results of 48 UMKM in Kabupaten Subang stated that they had utilized internet media such as promotions on Whatsapp, and Facebook. However, the business has not been comparable to sales before the pandemic. Some entrepreneurs also expressed a desire to sell products online, but limitations in knowledge and the lack of devices they currently have.  So there needs to be a workshops and assistance to several UMKM with four topics, that are marketing management, re-branding and updating product designs, the use of e-commerce,  and the use of financial management applications.  After the workshop,  it was continued with direct assistance by lecturers and several students to ensure that UMKM have utilized digital media and technology optimally. The last activity is monitoring and evaluation to see an increase in revenue after the use of digital media and technology